Preparation of a Si/SiO2–Ordered‐Mesoporous‐Carbon Nanocomposite as an Anode for High‐Performance Lithium‐Ion and Sodium‐Ion Batteries. Issue 19 (17th January 2018) - Zeng, Lingxing; Liu, Renpin; Han, Lei; Luo, Fenqiang; Chen, Xi; Wang, Jianbiao; Qian, Qingrong; Chen, Qinghua; Wei, Mingdeng
Abstract: In this work, an Si/SiO2 –ordered‐mesoporous carbon (Si/SiO2 –OMC) nanocomposite was initially fabricated through a magnesiothermic reduction strategy by using a two‐dimensional bicontinuous mesochannel of SiO2 –OMC as a precursor, combined with an NaOH etching process, in which crystal Si/amorphous SiO2 nanoparticles were encapsulated into the OMC matrix. Not only can such unique porous crystal Si/amorphous SiO2 nanoparticles uniformly dispersed in the OMC matrix mitigate the volume change of active materials during the cycling process, but they can also improve electrical conductivity of Si/SiO2 and facilitate the Li + /Na + diffusion. When applied as an anode for lithium‐ion batteries (LIBs), the Si/SiO2 –OMC composite displayed superior reversible capacity (958 mA h g −1 at 0.2 A g −1 after 100 cycles) and good cycling life (retaining a capacity of 459 mA h g −1 at 2 A g −1 after 1000 cycles). For sodium‐ion batteries (SIBs), the composite maintained a high capacity of 423 mA h g −1 after 100 cycles at 0.05 A g −1 and an extremely stable reversible capacity of 190 mA h g −1 was retained even after 500 cycles at 1 A g −1 . This performance is one of the best long‐term cycling properties of Si‐based SIB anode materials. The Si/SiO2 –OMC composites exhibited great potential as an alternative material for both lithium‐ and sodium‐ion battery anodes. Abstract : On the hunt for anode materials : Si/SiO2 –ordered‐mesoporous‐carbon (OMC) composite was initially fabricated through a magnesiothermic reduction strategy by using two‐dimensional bicontinuous mesochannel of SiO2 –OMC as a precursor, combined with a NaOH etching process. In addition the material exhibited great potential as an alternative material for both LIBs and SIBs anodes.